Analysing critical success factors for supporting online shopping - Varela, Maria Leonilde Rocha (2017)
Copying or distributing in print or electronic forms without written permission of IGI Global is prohibited. Online shopping is nowadays is a highly frequent action but there are several critical factors that have to be considered for enabling websites and platforms to be able to offer all necessary requisites for guaranteeing user friendly, secure and also enjoyable shopping experiences to clients, offering them exactly what they expect to buy, and quickly find, among a huge offer available online. In this paper, a set of considered critical success factors are analysed on a set of top ranked websites, about luxurious furniture, to understand to what extent these critical factors are satisfied. The results can be taken into consideration for implementing a successful business through e-commerce from herein analysed perspectives.